Utilization of Learning Videos Using Canva in Learning Social Studies - Rahmat Hidayat; Arif rahmatul Aji; Halimah Syutri (International Journal of Language and Ubiquitous Learning, 2023)
Background. This discussion is about the use of canva software as a thematic learning video for Class V Semester I Theme two Subtheme 1 Learning three at State Elementary School 05 IX Koto, Dharmasraya Regency Purpose The purpose of this research is to find out the development of students' needs for learning media in the form of animated videos using the Canva application in learning Social Studies (IPS). Method. The analysis carried out is to find out the use of media at the time of the teaching and learning process in Social Studies lessons online or virtually. The instrument used in this study uses a questionnaire or questionnaire with quantitative data types and is a closed questionnaire. This questionnaire is distributed via google form in the form of a link that students must fill out virtually. Results. The results of this analysis show that from 10 educators and 163 students in class IV (four) in nine elementary schools (SD) in Jakarta and Wonogiri prove that 90% of teachers state that they need and agree to use animated video media based on canva applications that are interesting, 90% of educators say they need and agree to use animated video media based on canva applications that are good and 83.4% of students say they need to use canva application video media in learning social studies (Social Studies). Conclusion. Based on the research, it can be concluded that there should be a development of animated video media based on the canva application in social studies learning.